Enhanced Buck Converter with Universal Model for the Switched Voltage Regulators - Dobroslav Kováč; Irena Kováčová (Communications)
This article presents the enhancement and refinement of a simulation model for an integrated universal switched voltage regulator compatible with PSPICE software. The model enables users to create representations of any specific type of switched voltage regulator currently available on the market. The described regulator model is practically applied in widely used configurations of buck converters, including applications in transportation. The accuracy of the regulator model is verified by comparing the simulated waveforms of the converter to those provided in its datasheet. Additionally, the model is employed for the design and simulation analysis of buck converter circuits, with extended current and voltage ranges for their output parameters. In the context of improving the performance of such converters, particular attention is given to enhancing their electromagnetic compatibility.